Navigating Indigenous heritage protection and local land use planning on the island of Xwe'etay, British Columbia - MacLean, Madeleine; Markey, Sean; Lepofsky, Dana (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2025)
In many contexts around the world, colonial-settler heritage policies and local planning processes contribute to the ongoing loss of Indigenous archaeological heritage (IAH). Many intertwined factors contribute to this loss, including colonial systems that do not recognize the inherent rights of Indigenous people to manage their heritage on their own terms. Here, we explore the challenges that heritage policies and local planning systems present to robust IAH conservation. We focus on the island of Xwe’etay, in the Salish Sea of British Columbia and the governing bodies that control or have an interest in its heritage. Our interviews with local planners, First Nations, and others inform three central issues foundational to IAH planning: 1) jurisdiction and planning scope; 2) regulation and enforcement; and 3) capacity and resource limitations. We find that top-down, colonial regulations that guide heritage management practices are failing to adequately protect Indigenous archaeological heritage, while also instilling uncertainty and fear among settler landowners. Engaging First Nation and settler community members in IAH conservation, active relationship-building, knowledge mobilization, and enhanced local jurisdiction may present pathways to better protect IAH.